(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Micro Small and Medium Enterprises are recognized as the engine of growth all over the world. The present paper deals with the marketing problems faced by micro small and medium enterprises in Thoothukudi District. The study has the following objectives 1. To study the socio-economic outline of the micro, small and medium entrepreneurs. 2. To find out the professional background of micro, small and medium entrepreneurs. 3. To understand the satisfaction of micro, small and medium industries among the sample respondents based on sex. 4. To analyse the marketing problems faced by the sample respondents.